Formulasi dan Evaluasi Produk Inovasi Balsem Sindrong Jangkep Dengan Penambahan Minyak Atsiri Nilam (Pogostemon Cablin Benth) - Lakustini Cahyaningrum, Putu; Ayu Made Yuliari, Sang; Bagus Putra Suta, Ida; Kadek Citra Lestari, Ni; Agung Istri Adi Suwi Setyawati, Anak (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
The complexity of infectious and non-communicable diseases has led to the development of traditional medicine. This is mediated by safety, side effects, and relatively cheaper prices. Medicinal plants have been developed in the form of sindrong jangkep balm products combined with patchouli essential oil (Pogostemon cablin Benth). The purpose of this study was to determine the formulation and evaluation of sindrong jangkep balm products combined with patchouli essential oil. Experimental research design with a completely randomized design. Three concentrations of sindrong jangkep were formulated, 1:1, 2:2, and 4:4, and analyzed for efficacy. The results of the physical quality evaluation of sindrong jangkep balm with the addition of patchouli essential oil as a whole have a distinctive odor of sindrong jangkep, pale yellow to brownish color, semi-solid texture, all homogeneous, have a spreadability between 5.50-5.85 cm with a stickiness of 3-5 seconds, and viscosity, between 56,000-63,000 cP. Chemical quality obtained pH for FI 6.74 ± 0.142 combination of sindrong jangkep oil and patchouli essential oil ratio 1:1; FII with pH 6.29 ± 0.075 ratio 2:2, and FIII with pH 5.32 ± 0.015 ratio 4:4 has met the requirements and is safe for skin preparations. Sindrong jangkep balm supplemented with essential oil fulfilled the prerequisites for balm preparation and is worth developing in the future.